2015
DOI: 10.1108/s1049-258520150000023008
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Disparities between Monetary and Multidimensional Poverty Measurement: Evidence from Vietnam

Abstract: This study has been prepared within the OPHI theme on multidimensional measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…Across nine European countries, Whelan, Layte, and Maître (2004) found mismatches between income poverty and material deprivation. Using longitudinal data for Vietnam, Tran, Alkire and Klasen (2015) observed that the overlap between income poverty and multidimensional poverty was even less than 50%. For further discussions on relevant studies, see , Ch 1.…”
Section: Non-monetary Standard Of Livingmentioning
confidence: 99%
“…Across nine European countries, Whelan, Layte, and Maître (2004) found mismatches between income poverty and material deprivation. Using longitudinal data for Vietnam, Tran, Alkire and Klasen (2015) observed that the overlap between income poverty and multidimensional poverty was even less than 50%. For further discussions on relevant studies, see , Ch 1.…”
Section: Non-monetary Standard Of Livingmentioning
confidence: 99%
“…Vietnam has been one of the most successful countries in the developing world in terms of economic growth and poverty reduction. he rapid economic growth, together with market liberalization and trade openness that took place during the last two decades, has lited a large share of the population out of poverty (see Tran, Alkire, and Klasen 2015). Nonetheless, poverty is still a central issue in the country as nearly 43 percent of the population still lives on less than $2 a day (World Bank 2013), and many people earn their living by engaging in agricultural activities.…”
Section: Income Diversity and Poverty Transitions: Evidence From Vietnammentioning
confidence: 99%
“…A few studies have investigated the role of household characteristics in explaining discrepancies between monetary and multidimensional poverty using survey data and regression modelling. Research in South Africa and Vietnam find that household size, gender and education of the household head and ethnicity are associated with varying levels of poverty mismatch (Klasen, 2000;Tran et al, 2015). With respect to children, a study in Tanzania found the degree of mismatch between monetary and non-monetary child poverty to be larger for lower levels of maternal education (Ballón et al, 2016).…”
Section: Individualistic Factorsmentioning
confidence: 99%
“…Migration as a result of lack of economic opportunities, for example, may lead to greater economic resources for the family but also leave children without parental care with potential negative consequences for wellbeing and care (Gassmann et al, 2013). Geographical indicators can be used as proxies to investigate the role of socioeconomic conditions, with studies finding differential poverty outcomes depending on residence in urban or rural areas or particular districts (Klasen, 2000;Tran et al, 2015).…”
Section: Structural Factorsmentioning
confidence: 99%
See 1 more Smart Citation